Sosialisasi Tentang Pengelolaan Sampah Dengan Prinsip 3R Dan Pembuatan Ecobrick - Apriyani; Suwignyo; Rindha Mareta Kusumawati; Kartina Wulandari (CV. Multi Kreasi Media, 2024)
This outreach focuses on community service as a response to findings in the literature review regarding waste management using the 3R principles in Indonesia and also making ecobricks as an effort to process waste so that it has useful value. Involving the community directly, service activities aim to implement the 3R principles in daily life and tell the community how to make ecobricks. In the context of community empowerment, this research notes positive behavioral changes that emerge from a participatory approach, such as increased awareness of waste management and active participation in sustainable practices. The results of this service offer in-depth insight into how involving the community directly can be the key to success in achieving sustainable waste management practices, forming a more environmentally conscious society, and creating a positive impact in the local economic context.